Foundations of the right to resistance starting with Hegel: tra seconda coercizione, diritto di necessità e vulnerabilità - Battistoni, Giulia (B@belonline, 2022)
Starting from the recent studies by Klaus Vieweg, this paper will discuss in what sense one can speak of a ‘right to resistance’ within Hegel’s Rechtsphilosophie. Taking as a textual reference the Elements of the Philosophy of Right (1821), but also the rich material made available by the Vorlesungen über die Philosophie des Rechts (1817/18 – 1824/25), I will identify the logical and juridical-rational foundation of the right to resistance in the ‘second coercion’ against an illicit behavior (2) and its moral foundation in the subjective right of each individual to the realization of their own welfare and in the right of necessity connected to it (3). This will lead to consider the meaning of resistance in the context of a political order that does not promote freedom and personal rights (4), and to finally address the interesting perspective developed by Judith Butler (5), which allows to move «with Hegel beyond Hegel», integrating the conditions of the right to resistance identified by him with Butler’s idea of ​​a «mobilization of vulnerability».